2014
DOI: 10.1007/s10201-014-0425-4
|View full text |Cite
|
Sign up to set email alerts
|

Spatial distribution of epiphytic chironomid larvae in a shallow macrophyte-dominated lake: effect of macrophyte species and food resources

Abstract: Four submerged macrophytes were analysed with their respective assemblages of chironomid and algal taxa. Studies were made bimonthly, from January to November, in a shallow macrophyte-dominated lake. The periphytic algal community was represented by chlorophytes, diatoms and cyanobacteria; diatoms showed the highest relative abundance on the macrophyte species during the study. Algal biomass was affected by the season, and in January the highest values were found on Stratiotes aloides L., Potamogeton lucens L.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(8 citation statements)
references
References 61 publications
1
7
0
Order By: Relevance
“…Moreover, the habitat preferences of larval chironomids in a shallow clear-water lake are related to the biomass of periphytic algae on host plants and to environmental variables (oxygen, nutrients) specific to the macrophyte stand (Vermaire et al, 2013;Tarkowska-Kukuryk, 2014). This relationship is consistent with numerous contemporary studies that have documented a relationship between chironomid community assemblage and macrophyte abundance (Langdon et al, 2010;Vermaire et al, 2013;Tarkowska-Kukuryk, 2014).…”
Section: Human Impacts: Increasing the Complexity Of Paleolimnologicasupporting
confidence: 82%
See 1 more Smart Citation
“…Moreover, the habitat preferences of larval chironomids in a shallow clear-water lake are related to the biomass of periphytic algae on host plants and to environmental variables (oxygen, nutrients) specific to the macrophyte stand (Vermaire et al, 2013;Tarkowska-Kukuryk, 2014). This relationship is consistent with numerous contemporary studies that have documented a relationship between chironomid community assemblage and macrophyte abundance (Langdon et al, 2010;Vermaire et al, 2013;Tarkowska-Kukuryk, 2014).…”
Section: Human Impacts: Increasing the Complexity Of Paleolimnologicasupporting
confidence: 82%
“…This could be associated with the vegetation, which is important for the benthic community because it provides physically stable habitats, better food conditions, refuge from predators, and higher concentration of dissolved oxygen (Takamura et al, 2009). Moreover, the habitat preferences of larval chironomids in a shallow clear-water lake are related to the biomass of periphytic algae on host plants and to environmental variables (oxygen, nutrients) specific to the macrophyte stand (Vermaire et al, 2013;Tarkowska-Kukuryk, 2014). This relationship is consistent with numerous contemporary studies that have documented a relationship between chironomid community assemblage and macrophyte abundance (Langdon et al, 2010;Vermaire et al, 2013;Tarkowska-Kukuryk, 2014).…”
Section: Human Impacts: Increasing the Complexity Of Paleolimnologicamentioning
confidence: 99%
“…The intermediate zone at Taro Co is characterized by Paratanytarsus, a genus associated to macrophytes (Beckett et al, 1992, Tarkowska-Kukuryk, 2014. In a study on several lakes of the Plymouth Aquifer, Engels and Cwynar, (2011) found it connected to shallow water up to 10 m water depth.…”
Section: Taro Comentioning
confidence: 99%
“…In our study, the diatoms belonging to Caloneis amphisbaena, Cymatopleura solea, Navicula sp., and Encyonema minutum were found at almost every sampling location. Although diatoms are foods with rich protein, green algae also have rich protein, including essential fat oils that are needed for larvae growth [44,45,46]. The role of algae in chironomid diets could be related to the phenology of T. punctipennis in the study area.…”
Section: Resultsmentioning
confidence: 99%